Tenure Security Premium in Informal Housing Markets: A Spatial Hedonic Analysis. (January 2017) - Nakamura, Shohei
Highlights: This study estimates slum residents' marginal willingness to pay for formalized land tenure in Pune. In its hedonic approach, this study uses spatial econometrics models to deal with spatial effects. Estimated MWTP is worth 19% of the average rent in the Pune slums and higher in privately owned land. The willingness to pay varies depending on caste, duration of residence, and legal conditions. Summary: This paper estimates slum residents' willingness to pay for formalized land tenure in Pune, India. The results show that the legal assurance of slum residents' occupancy of their lands could benefit them. Previous studies have discussed the legal and non-legal factors that substantially influence the tenure security of residents in informal settlements; however, it remains unclear how and to what extent the assignment of legal property rights through the formalization of land tenure improves the tenure security of residents in informal settlements and living conditions, even in the presence of other legal and non-legal factors that also contribute to their tenure security. To address this question, this study focuses on the city of Pune, India, where government agencies have formalized slums by legally ensuring the occupancy of the residents under the "slum declaration." Applying a hedonic price model to an original household survey, this paper investigates how slum residents evaluate formalized land tenure. A spatial econometrics method is also applied to account for spatial dependence and spatially autocorrelated unobserved errors. The spatial hedonic analysis shows that the premium of slum declaration is worth 19.2% of the average housing rent in slums. The associated marginal willingness to pay is equivalent to 6.7% of the average household expenditure, although it is heterogeneous depending on a household's caste and other legal conditions. This finding suggests that the assurance of occupancy rights is a vital component of land-tenure formalization policy even if it does not directly provide full property rights.